Manajemen Strategi Pendidikan Pesantren dalam Mempersiapkan Era Indonesia Emas 2045 di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Imam Mukhrozi; Nurul Hidayati Murtafiah; Cipto Handoko (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The purpose of this study is to analyze in depth how the management of Islamic boarding school education strategies at the Hidayatul Mubtadiin Jati Agung South Lampung Islamic Boarding School can be effectively prepared to face the Golden Indonesia 2045 era, with a focus on strengthening student competencies, integrating religious values ??and 21st-century skills, and involving internal and external stakeholders. This study uses a qualitative approach with a case study design to explore the management of educational strategies at the Hidayatul Mubtadiin Islamic Boarding School in preparing for the Golden Indonesia 2045 era. The research subjects were selected purposively, including the head of the Islamic boarding school, teachers, administrators, students, parents, and community leaders. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed thematically. This study shows that strategic educational management at the Hidayatul Mubtadiin Jati Agung South Lampung Islamic Boarding School plays a crucial role in preparing students for the Golden Indonesia era in 2045. A holistic and integrative approach through strategic planning, an adaptive curriculum that combines religious values ??and 21st-century skills, and teacher competency enhancement creates an adaptive, innovative, and competitive educational ecosystem. This strategy equips students with digital literacy, leadership, collaboration, and entrepreneurship, while maintaining religious character. The findings confirm that the synergy between strategy, curriculum, and educator quality is key to the success of Islamic boarding schools in producing competent, creative graduates who are ready to compete nationally and globally, without losing their Islamic identity.